PSYCHOLOGICAL ASPECTS OF CONDUCTING A DIAGNOSTIC INTERVIEW IN THE FORMATION OF A RELIGIOUS PERSON AND HIS STUDY - Akramov Mirmukhsin Rustamovich (Western European Studies, 2025)
This article discusses the individual-psychological, family, socio-psychological factors in the formation of a personality, as well as the issues of a fanatical person's worldview, intolerance towards those of other faiths, disregard for the opinions of others, and denial of alternative views. It also describes in detail the socio-psychological factors that influence the formation of a fanatical person, the psychological aspects of the diagnostic interview conducted with them, and the importance of this
Keywords: person; fanatical; psychological aspects